Estimation of heterosis and combining ability in interspecific cotton hybrids - Abasianyanga Isong; Amala Balu; Chioma Isong and; Eunice Bamishaiye (Electronic Journal of Plant Breeding, 2019)
Investigation was to assess heterosis, general and specific combining ability for seed cotton yield, yield contributing traits and fibre quality parameters in interspecific F1 hybrids of cotton. 45 hybrids along with their parents and a standard commercial variety using randomized complete block design were evaluated for per se performance, heterosis and combining ability potential. Significant variation existed among the genotypes, crosses, parents and their interactions. Hybrid TCH1819 x TCB37 was outstanding in yield followed by COD-5-1-2 x DB3 and KC2 x TCB37. TCH1705-101 x CCB36 performed best in number of seeds per boll, fibre fineness and plant height, while TCH1819 x TCB209 out performed in uniformity ratio and elongation per cent. The highest standard and better heterosis of 90.6% and 193.69% respectively were recorded in TCH1819 x TCB37 for seed cotton yield. The combining ability analysis showed an equal importance of additive and non-additive genetic components in yield contributing traits and fibre quality parameters. The lines TCH1819, COD-5-1-2, VS-9-S11-1 and MCU7 and testers DB3 and TCB37 were distinguished as best combiners. Surabhi x TCB209, TSH0250 x CCB36, VS-9-S11-1 x DB3 and TCH1705-101 x DB3 were identified as best specific combiners and may be recommended for further breeding program